Experimental characterisation of ultra‐wideband off‐body radio channels considering antenna effects. Issue 5 (1st April 2013) - Khan, Mohammad Monirujjaman; Abbasi, Qammer Hussain; Alomainy, Akram; Hao, Yang; Parini, Clive
Abstract : Experimental investigation to characterise the ultra‐wideband (UWB) off‐body radio propagation channel for body‐centric wireless communication is presented. The measurements were performed in an indoor environment using active UWB wireless tags. Two different kinds of receiver antennas have been used; namely a small form factor (SFF) antenna and miniaturised co‐planar waveguide‐fed tapered slot antenna to investigate their effects on the radio channel behaviour. Statistical analysis is performed on the radio channel data and the results demonstrated that the lognormal distribution provides the best fit for off‐body propagation channel path‐loss models. Comparison of results shows that a reduction of 29% path‐loss exponent is noticed for the SFF antenna. In addition to this, second‐order channel parameters such as fade probability, level‐crossing rate and average fade duration are also investigated and compared for the two antennas.